INTERTEXTUAL ANALYSIS OF PRAYER POETRY BY CHAIRIL ANWAR AND TAUFIK ISMAIL'S WORK - Juwaeni, Juwaeni; Lisa Riskiawati, Hila; T. Collins, James (ASMARALOKA: Jurnal Bidang Pendidikan, Linguistik, dan Sastra Indonesia, 2023)
This study aims to describe the similarities and differences in Chairil Anwar's prayer poem and Taufik Ismail's prayer poem using an intertextual approach. These two poems have the same divine theme. The method used in this study is a qualitative descriptive research method, in which the researcher analyzes it descriptively and the results obtained are in accordance with the facts. The object of this study is the prayer poem by Chairil Anwar and Taufik Ismail. The sources of data obtained are several articles, journals, ebooks and books that discuss discourse, intertextual studies and poetry. In addition, there are techniques used in this study, namely reading and underestimating and taking notes. The results that have been obtained are two data bthat have similar motifs and the poems written by Chairil Anwar and Taufik Ismail.